2018
DOI: 10.1186/s12889-018-5841-7
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with multiple job holding: a qualitative study among Dutch older workers

Abstract: BackgroundMultiple job holding (MJH) is a common and growing phenomenon in many countries. Little is known about experiences with MJH among older workers. The objective of the present study is to gain insight in experiences with MJH among Dutch workers aged 45 years and older.MethodsMultiple job holders were selected from the Study on Transitions in Employment, Ability, and Motivation (STREAM), a Dutch cohort study among persons aged 45 years and older. Purposive sampling was applied to assure heterogeneity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…In contrast to this vulnerable group of multiple-job holders, other groups of multiple-job holders experienced benefits from holding multiple jobs (9). These findings have been confirmed in a qualitative study in which we found that some multi-jobbers only experienced benefits of multiple-job holding, eg, positive spill-over effects between jobs: networks established or skills learned in one job that can be used in others (10).…”
Section: Letter To the Editorsupporting
confidence: 78%
“…In contrast to this vulnerable group of multiple-job holders, other groups of multiple-job holders experienced benefits from holding multiple jobs (9). These findings have been confirmed in a qualitative study in which we found that some multi-jobbers only experienced benefits of multiple-job holding, eg, positive spill-over effects between jobs: networks established or skills learned in one job that can be used in others (10).…”
Section: Letter To the Editorsupporting
confidence: 78%
“…In addition, vulnerable multiple job holders had lower levels of mastery and worse household financial situation than multiple job holders in other groups. Previous qualitative research has suggested that feelings of mastery and a favorable financial situation are important resources for multiple job holders, enabling them to change their work situation, e.g., find one or more different jobs, if they are dissatisfied (Bouwhuis et al 2018). Policies aimed at increasing these resources, e.g., life-long learning (Van Der Heijden et al 2009), may improve sustainable employability among vulnerable multiple job holders, since it may provide them with skills and self-efficacy needed to find a different job.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the size of our study population, we have chosen to use 5% as a threshold for usefulness, which equals a minimum of N = 35 respondents in each class. Interpretability is related to the extent to which individual classes and the overall k classes solution are interpretable in light of earlier research or hypotheses on groups of multiple job holders (Bouwhuis et al 2018;Rouault 2002).…”
Section: Analysesmentioning
confidence: 99%
See 2 more Smart Citations